Housing policy in the social and economic sphere. Housing policy relationships and other specific policies - Sylwester Bogacki; Wińczysław Jastrzębski; Agnieszka Laskowska (Journal of Modern Science, 2023)
Abstrakt Housing policy aspiring to have a general social impact, subtracting from the scale of the state, like any other policy in this scope, is conducted in the European Union countries by the public sector. This sector remains a significant point of reference for this policy. The activity of the public sector in the countries of post-war Western Europe varies in intensity over time and is carried out at different spatial levels - also in relation to housing. The public sector has been subject to a tendency towards apparent self-limitation for at least the last four decades. This occurs mainly by reducing the importance of the state and its agencies in socio-economic development. Housing policy is one of the important sectoral policies of the state - including the government and local authorities - engaging public entities, political and social organizations and private entities to achieve the main and long-term goals in the area of housing, which are: creating conditions for purchasing or renting apartments by all citizens; ensuring the availability of the housing stock, i.e. implementing an appropriate scale of housing investments using primarily the market mechanism, and supporting the appropriate quality of the housing stock throughout the entire period of use of the property.